2023
DOI: 10.1002/jrs.6535
|View full text |Cite
|
Sign up to set email alerts
|

In situ thermo‐Raman spectroscopy and ab initio vibrational assignment calculations of cubanite CuFe2S3

Abstract: In situ thermo‐Raman spectroscopy is used to study a single crystal of natural orthorhombic cubanite from the Talnakh copper‐nickel sulfide deposit (Norilsk, Russia). The dependence of the wavenumbers and FWHMs of vibrational modes on temperature, including the cubanite → isocubanite phase transition region, is studied in the range of 83–873 K. For the first time, the polarized Raman spectra of cubanite have been interpreted according to ab initio calculations performed using the density functional theory (DFT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 55 publications
0
2
0
Order By: Relevance
“…It should be noted that the normal thermal shift toward lower wavenumbers is also typical for other lithium battery electrode materials, namely, LFP 29 and LCO. 30 Characteristic Raman bands of sodium battery materials 31,32 and of many other materials [33][34][35] also demonstrated such a behavior.…”
Section: Measurements Of Single Lto Particles Above Room Temperaturementioning
confidence: 95%
“…It should be noted that the normal thermal shift toward lower wavenumbers is also typical for other lithium battery electrode materials, namely, LFP 29 and LCO. 30 Characteristic Raman bands of sodium battery materials 31,32 and of many other materials [33][34][35] also demonstrated such a behavior.…”
Section: Measurements Of Single Lto Particles Above Room Temperaturementioning
confidence: 95%
“…The innovative novel dyad for FRET is formed from sulfonyl benzoxadiazole (SBD) and coumarin chromophore that relates to a rigid group of piperazine, and this configuration serves as a dual-channel signal reporter for fluorescence and the chlorine unit located at the 4-position of chromophore SBD acts as the Cys specific recognition site. The author observed that FRET is activated when probe Cou-SBD-Cl is exposed for Cys, and a fresh yellow fluorescence emission with a remarkable 56.1-fold increased radio signal and a significant 99 nm emission shift is produced . Therefore, the author has developed ratiometric Cou-SBD-Cl fluorescent probes that followed the Cou-SBD FRET mechanism for the specific identification of Cys, which can be seen in Figure …”
Section: Aromatic Substitution Rearrangement Sensing Mechanismmentioning
confidence: 99%